Assessment of Semen Quality among Workers Exposed to Heat Stress: A Cross-Sectional Study in a Steel Industry - Masoud Hamerezaee; Somayeh F. Dehghan; Farideh Golbabaei; Asad Fathi; Loghman Barzegar; Naseh Heidarnejad (Elsevier, 2018)
Background: This study was conducted to investigate the heat stress and semen quality among male workers in a steel industry in Iran and investigate the relationship between heat stress indices and semen parameters. Methods: The study was conducted on workers exposed (n = 30) and unexposed (n = 14) to heat in a steel industry. After obtaining a brief biography of the selected employees, scrotal temperature, oral temperature, and environmental parameters were measured, and their semen samples were analyzed according to the procedure recommended by the World Health Organization. The heat stress indices, including wet-bulb globe temperature (WBGT) and predicted heat strain (PHS), in their workplace were calculated according to environmental parameters (ISO 7243:1989 and 7933:2004, respectively). Results: Time-weighted averages of WBGT and PHS (35.76°C and 491.56 w/m2wm2, respectively) for the exposed group were higher than threshold limit values. The mean difference of environmental, physiological, and semen parameters (exception: pH of semen), and also WBGT and PHS indices were statistically significant (p < 0.05) between the two groups. Mean semen parameters were in the normozoospermic range. WBGT and PHS indices showed significantly "negative" correlation with physiological parameters (scrotal and oral temperature) and most semen parameters (semen volume, sperm morphology, sperm motility, sperm count; p < 0.05); moreover, the correlation of WBGT with these parameters was stronger than PHS. Conclusion: Semen parameters of the studied workers exposed to heat were in the borderline level of normozoospermic range, and their semen parameters were significantly lower than controls. For better assessment of occupational environment concerning physiological and semen parameters in steel industries, WBGT can be a more useful index. Keywords: heat stress, predicted heat strain, semen parameters, steel industry, wet-bulb globe temperature